IDENTIFIKASI KULIT IKAN BUNTAL (Arothon reticularis) MENGGUNAKAN SCANNING ELECTRON MICROSCOPE (SEM) - RLM. Satrio Ari Wibowo; M. Wahyu Syabani (Politeknik ATK Yogyakarta, 2015)
The goal on this research is to known the characteristic of skin of puffer fish. The material that used was dry salted skin of •puffer fish (Ara thon reticularis) and the methods was Scanning Electron Microscope (SEM). SEM can checking materials microscopically to help explain characteristic of physical material. The result of this research is there is spines of puffer fish that firm and penetrate from epidermis unto dermis and becoming one on dermis. The differences between spines of puffer fish and hairs on mammals are there is no follicles that connecting the skin with spines due differences of composition compiler. Identification using SEM shows spines of puffer fish is modification of collagen that can be join with collagen at epidermis to dermis. For this reason the tanners could exploring skin of puffer fish as raw material in leather industries because the uniqueness of skin of puffer fish.